Voices of Pupils on Educational Programme Under Corporate Social Responsibility Initiatives in Malaysia - Athirah Azhar (International Journal of Pedagogy and Teacher Education, 2023)
This study examined Corporate Social Responsibility (CSR) educational programmes in elementary schools. The case study examines the Adopt-A-School (AASC) programme, a CSR educational programme that is organised throughout Malaysia. Most extant studies have focused on teachers, school and corporate views but rarely on children. Therefore, this study aimed to explore pupils’ perceptions of CSR educational programmes in rural schools under the CSR initiative. The study employed a qualitative research case study design. Purposive sampling was conducted involving six Focus Group Discussions (FGDs) among 12-year-old pupils. Each FGD contained six to eight pupils. A total of 43 pupils from three different schools in the northern region of Malaysia were involved in the FGDs. Thematic analysis was then used to consider the excitement of CSR educational programmes, the benefits of CSR educational programmes and pupils’ preferred type of CSR educational programme in school. From the results, pupils’ perceptions of CSR educational programmes were divided into three: emotional well-being, cognitive ability and motor coordination. The engagement of the corporate sector in pupils’ education was also discussed to improve CSR educational programmes in future. The pupils agreed that while formal learning is important, a balance should be struck between study and play. Pupils requested that a CSR educational programme is conducted in school more often to make learning and attending school amusing. In conclusion, the pupils preferred to engage with more physical programmes in school but also acknowledged the importance of academic study as educational programmes bring them fun, friends, knowledge, experience and skills.